Cloud security and privacy. - Mather, Tim, ....-; Kumaraswamy, Subra, ....-; Latif, Shahed, ....- (Beijing : O'Reilly, 2009)
This authoritative book is the first resource to help IT personnel navigate tricky security and privacy issues associated with cloud computing. Cloud computing has emerged as a popular way for corporations to cut IT infrastructure costs. But along with the promise of cloud computing, there has also been considerable skepticism about the type and extent of security and privacy options available with these services. This book, written by recognized authorities in the tech security world, addresses issues that affect any organization preparing to use cloud computing as an option.